Come Out of a Hiding Place: How Are Cover Crops Allocated on Finnish Farms? - Peltonen-Sainio, Pirjo; Jauhiainen, Lauri (MDPI AG, 2022)
Cover crops (CCs) may provide many ecosystem services for crop production systems, and interest has increased in the cultivation of CCs among Finnish farmers. Piloting farmers applied for agricultural payments to support the cultivation of CCs (AP-CCs) in 2020. Novel data with a total of 34,515 field parcels with CCs from 5747 farms was used to assess how farmers allocated CCs depending on farm and parcel characteristics. Pioneering farmers often had conventional, large farms with cereal areas exceeding 25%, and expertise with special crop(s). Conventional farmers seemed to allocate CCs to large parcels. The allocation of CCs was not solely dictated by cash crops. Cover crops were planted more frequently in parcels close to waterways. Conventional farmers allocated CCs to parcels with a history of highly monotonous cereal sequencing. Hence, farmers seem to benefit from ecosystem services provided by CCs: increasing spatial diversity, reducing the environmental footprint, and improving soil health. This novel understanding is used to support the implementation of CCs beyond pilot farms and to develop a decision support system for their allocation. The ultimate goal is to support a transition towards more sustainable crop production systems with currently underutilized CCs in high-latitude conditions.
Keywords: cover crop; cash crop; crop rotation; diversification; farming system; field parcel; land allocation; region